2012
DOI: 10.3389/fpls.2012.00291
|View full text |Cite
|
Sign up to set email alerts
|

The induction of stromule formation by a plant DNA-virus in epidermal leaf tissues suggests a novel intra- and intercellular macromolecular trafficking route

Abstract: Stromules are dynamic thin protrusions of membrane envelope from plant cell plastids. Despite considerable progress in understanding the importance of certain cytoskeleton elements and motor proteins for stromule maintenance, their function within the cell has yet to be unraveled. Several viruses cause a remodulation of plastid structures and stromule biogenesis within their host plants. For RNA-viruses these interactions were demonstrated to be relevant to the infection process. An involvement of plastids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 143 publications
(252 reference statements)
3
71
1
Order By: Relevance
“…Stromules have been found to be induced by effector-triggered immunity, and chloroplastlocalized N receptor-interacting protein1 (NRIP1) was transported from chloroplasts into the nucleus during this process through stromules (Caplan et al, 2015). Moreover, in Abutilon mosaic virus-infected leaves, a plastid-targeted heat shock cognate 70-kD protein (chaperone) was found to interact with Abutilon mosaic virus movement protein in the stromules (Krenz et al, 2010), which may facilitate viral transport from chloroplasts into a neighboring cell or the nucleus (Krenz et al, 2012). Therefore, the stromule conduits may be a pathway by which ZmVDEm is transported from chloroplasts back into the cytoplasm upon SCMV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stromules have been found to be induced by effector-triggered immunity, and chloroplastlocalized N receptor-interacting protein1 (NRIP1) was transported from chloroplasts into the nucleus during this process through stromules (Caplan et al, 2015). Moreover, in Abutilon mosaic virus-infected leaves, a plastid-targeted heat shock cognate 70-kD protein (chaperone) was found to interact with Abutilon mosaic virus movement protein in the stromules (Krenz et al, 2010), which may facilitate viral transport from chloroplasts into a neighboring cell or the nucleus (Krenz et al, 2012). Therefore, the stromule conduits may be a pathway by which ZmVDEm is transported from chloroplasts back into the cytoplasm upon SCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast stromules, which are thin projections of stroma-filled tubules emerging from the surface of chloroplasts, have been reported to be associated with abiotic and biotic stresses (Gray et al, 2012;Krenz et al, 2012;Caplan et al, 2015). Although the biological significance of stromules remains unclear, accumulating evidence indicated that the stromules function in trafficking proteins (Krenz et al, 2012;Hanson and Sattarzadeh, 2013;Caplan et al, 2015). Stromules have been found to be induced by effector-triggered immunity, and chloroplastlocalized N receptor-interacting protein1 (NRIP1) was transported from chloroplasts into the nucleus during this process through stromules (Caplan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Stromule induction has been observed in relation to biotic stresses like plant viral infection (Krenz et al, 2012) and abiotic stresses like heat (Holzinger et al, 2007). In many instances, stromules were observed in close contact with nuclei (Kwok and Hanson, 2004;Holzinger et al, 2007;Caplan et al, 2015).…”
Section: Reinterpreting the Effect Of Aba On Stromule Formationmentioning
confidence: 98%
“…The cpHSC70-1-containing stromules detected upon an Abutilon mosaic virus (AbMV, plant ssDNA virus, Geminiviridae)-infection that was also in close association with the nucleus, appeared to interconnect plastids and extended from plastids outward to the cell periphery. This led to speculations of intra-and intercellular geminiviral transport in association with stromules [22,23]. A geminiviral nucleoprotein complex moves out of the plant nucleus via plasmodesmata into the adjacent cell to systemically infect the plant.…”
Section: Stromule Formation Upon Plant Virus Infectionmentioning
confidence: 99%
“…Other constructs have also been reported to visualize stromules, e.g. chloroplast-localized heat shock cognate 70-kDa protein (cpHSC70-1) [22,23], outer envelope protein 16 -2.1, -2.2 and -1.3 [24] and mutants of the Arabidopsis resistance protein RPW8.2 [25].…”
Section: Stromule Markersmentioning
confidence: 99%